Malaria - changing paradigms - Cox-Singh, Janet (Henry Stewart Talks, 2016)
Malaria statistics 2015, Malaria incidence 2000 to 2015, Causative agents of malaria, life cycle and transmission, Malaria diagnosis and treatment WHO guidelines, Artemisinins to treat malaria, combination therapies and the emergence of drug resistance, Non-falciparum malaria